Genomics and transcriptomics analyses provide insights into the cold adaptation strategies of an Antarctic bacterium, Cryobacterium sp. SO1 - Cheah, Y. K.; Teoh, C. P.; Lavin, P.; Lee, D. J. H.; González-Aravena, M.; Najimudin, N.; Lee, P. C.; Wong, C. M. V. L. (Springer Science and Business Media LLC, 2021)
Thirteen out of the 15 known Cryobacterium spp. were from extremely cold environments. However, the fundamental question on their cold adaptation strategies to survive in the cold has not been addressed adequately. Hence, this work was conducted to determine the Cryobacterium sp. SO1 cold adaptation strategies. Cryobacterium sp. SO1 that grew optimally at 20 °C was exposed to a sub-optimal temperature of 10 °C. Its mRNA was extracted, sequenced, and analyzed. Strain SO1 global transcriptional profiles revealed a total of 182 differential expressed genes. Four hydrolases, a clp protease, and novel YraN family endonuclease that were related to the programmed cell death pathway were upregulated, indicating that the temperature drop was probably lethal to some cells. Three highly upregulated transcriptional regulators were likely to be the key components to regulate genome-wide expression to adapt to the cold. Meanwhile, the oligo-ribonuclease and a Clp protease gene were upregulated probably to remove accumulated misfolded mRNA and proteins, respectively. The SerB gene was upregulated probably to provide more L-serine residue for the biosynthesis of cold-adapted proteins. Interestingly, most of the stress protein genes in the genome, such as the reactive oxygen species (ROS)-scavenging enzymes were not upregulated. Instead, strain SO1 upregulated the six ribosomal genes which were the target of oxidative nucleobase damage caused by the ROS. This mechanism was probably to ensure that the protein biosynthesis machinery was not affected. Overall, strain SO1 had all the necessary genes and well-coordinated mechanisms to adapt to the sub-optimal growth temperature.